Penerapan Model Pembelajaran Langsung untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Matematika di Masa Pandemi Covid-19 Siswa Kelas VI SDN 71 Manado - Ruddy A. Tompunu (Peneliti.net, 2021)
The purpose of this study was to improve learning outcomes in mathematics learning through the application of direct learning models to Class VI students of SDN 71 Manado. The type of research carried out is classroom action research. The classroom action research method used in this study is a spiral model. In the spiral model, the research stages are divided into four stages, namely planning, action, observation, and reflection stages, and so on until the expected improvement or improvement is achieved. The data collection technique used in this research is through observation and tests. Data analysis techniques in this study include qualitative data analysis techniques and quantitative data. This research can be said to be successful if there is an increase in the activity and learning outcomes of class VI students in mathematics in each cycle from a predetermined minimum completeness criterion value of 65. Individual students are considered to have completed learning if students are able to get a score of at least a score of 65 and Student learning activities are considered complete if they increase classically by 75%. The direct learning model can improve the learning outcomes of sixth grade elementary school students. This is shown in the first cycle obtained classical completeness of 60.67% and in the second cycle increased with classical completeness of 94%. The direct learning model is a learning model that will help students learn and master the subject matter and has proven successful in improving learning outcomes.